Pattern of Disinfection of Root Canal Dentin by Alternated Acid-Base Irrigating Regimen - Janir Alves Soares; Maria Auxiliadora Roque de Carvalho; Suelleng Maria Cunha Santos Soares; Rodrigo Dantas Pereira; Manoel Brito-Júnior; Paula Prazeres Magalhães; Isabel Alessandra Miranda Nunes; Rudys Rodolpho de Jesus Tavarez; Claudia de Castro Rizzi; Rafaela Nogueira Moreira; Luiz de Macêdo Farias; Etevaldo Matos Maia Filho (The Scientific World Journal)
Objective. To quantify Enterococcus faecalis density in root canal dentin after chemomechanical preparation (CMP) using alternated irrigating regimen. Methodology. Root canals (RC) were contaminated with E. faecalis (ATCC 19433) for 3 weeks and evident biofilms were obtained. After initial sampling (S1), the CMP was aided by irrigants: saline solution (control; n=12), a conventional regimen (CR) (group 1; n=12) using 5.25% NaOCl and a final rinse with 17% EDTA, and an alternating regimen (AR) of intercalated use of NaOCl and EDTA (group 2, n=12), followed by a second sampling (S2). After 2 weeks, S3 was obtained. Two roots were analyzed by scanning electron microscopy. Each root was divided into cervical, mild, and apical segments and sampling of the superficial (n=90) and deep (n=90) dentin layers was obtained using Gates-Glidden burs. The E. faecalis density (CFU/mg) in log10 was categorized as residual (0 > 0.2), moderate (0.2 ≥ 0.5), or elevated (> 0.5). The prevalence of positive samples in BHI and BHI-A was analyzed by Pearson’s chi-square test. The data were normalized by a log10 transformation of CFU and were analyzed by one-way ANOVA and Tukey’s tests. Results. Biofilms were observed only in the control root canal walls. Topographically, the controls and CR showed similar distributions of E. faecalis in the dentin. Microbiologically positive root canals harbored much E. faecalis in the adjacent dentin (p < 0.05). Irrigating saline provided moderate density of E. faecalis in the dentin while CR and AR resulted in a residual density of microorganisms (p < 0.05). Conclusions. The Enterococcus faecalis density in dentin was influenced by the irrigating regimen and the microbiological status of the root canal. The CMP aided by the alternating regimen interfered with the recolonization of the root canal and topographic distribution of Enterococcus in root dentin.